Behavioral Analysis of Household Waste Management with ISPA Incidences in Sukowetan Village, Karangan Trenggalek Regency - Nindi Monic Sevela; Mayta Sari Dwianggimawati (Universitas STRADA Indonesia, 2021)
Acute Respiratory Infection (ARI) lasts for 14 days and is a respiratory infection caused by a virus or bacteria. The purpose of this study was to determine the effect of household waste management behavior on the incidence of ARI in Sukowetan Village, Karangan District, Trenggalek Regency.This study used a cross sectional design. The population is all 155 houses in Sukowetan Village, Karangan District, Trenggalek Regency. The sample is 112 houses with simple random sampling technique. The independent variable is the behavior of household waste management, while the dependent variable is the incidence of ARI. The results of this study were analyzed with logistic regression.The results of this study found that most of the respondents had low category household waste management behavior as many as 87 respondents (86.6%). Nearly half of the respondents did not experience ARI incidence, namely as many as 99 respondents (88.4%). There is a relationship between household waste management behavior and the incidence of ARI in Sukowetan Village, Karangan District, Trenggalek Regency (p value 0.003 <0.05).If the management of household waste is better, the lower the incidence of ARIs. The community should better manage waste in a proper and correct way so as to reduce the incidence of ARI.